Domestic violence in Appalachian newspaper coverage: minimizing a problem or mobilizing for a solution?. Issue 1 (2nd January 2021) - Seely, Natalee; Riffe, Daniel
ABSTRACT: Social and physical isolation, gender roles, cultural values, and poverty associated with the Appalachian region of the United States may shape how domestic violence is identified, discussed and addressed. This analysis identifies framing devices, sourcing, and mobilizing information within domestic violence news coverage across Appalachia, and compares coverage in three "economic status" regions marked by higher rates of poverty and unemployment. Societal and statistical context was rare: only 1 in 10 articles contained thematic framing elements. Police sources—often part of a "just the facts" narrative—were present in 80% of articles, while victim advocates were cited in 8% of coverage. Victims' own voices were even more obscured, found in less than 2% of articles. Around 10% of news stories contained some type of mobilizing information such as for hotlines or shelter information.